Improving Competence with Business Competition Management Applications: Study on Customs Services Management Entrepreneurs in The Soekarno Hatta Airport Area, Jakarta - Dudi Rudianto; Dominica A. Widyastuti; Holila Hatta; Berkah I. Santoso (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
This research aims to develop Business Competition Management Applications to Improve Competitiveness. Researchers use customs service business actors in the Soekarno Hatta Airport, Jakarta. The research method uses an action research approach by mapping the existing problems at the research locus and then developing problem solutions to minimize the risk of loss due to the competitive level of competition. The research results describe the problems at the research locus and produce Business Competition Management Applications as an early warning system and self-assessment to assess business competitiveness and what solutions companies must take to get out of these difficulties. The novelty of this research is in the form of Business Competition Management Applications that customs service business actors can implement. The implications of this research are to positively contribute to customs service businesses as an early warning system and self-assessment to minimize the risk of business bankruptcy.